DAMPAK PERCERAIAN ORANG TUA TERHADAP PRESTASI BELAJAR ANAK PADA MATA PELAJARAN AGAMA ISLAM - nurdiana -; Nurdiana, Nurdiana (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2022)
The research ’’Impact of Parental Divorce on Children’s Learning Achievement in Islamic in Kamalaputi Village, East Sumba Regency’’ with problems regarding parental divorce can affect children’s learning achievement in Islamic education in East Sumba Regency and the divorce factors that can affect children’s learning achievement in Islamic education in East Sumba Regency. reduce children’s learning achievement in Islamic in East Sumba Regency. The purpose of this study is to find out what factors reduce children’s learning achievement in Islamic and to find out whether parental divorce can affect children’s Islamic education achievement. Field research method with qualitative type is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. Data sources are primary data and secondary data Divorce has a very big impact on children, especially on their religious achievements, especially Islamic Religious Education. Children who are victims of divorce feel ashamed of their friends, they must think that their friends will talk about it at school or outside of school or so often to be alone, fear, worry, sadness, anger, discomfort and jealousy that is felt will really interfere with concentration. their learning, so that children’s achievement decreases, especially in Islamic education. Keywords ; Impact of Divorce, Learning Achievement.